Agromyces agglutinans sp. nov., isolated from saline lake sediment. Issue 1 (27th January 2022) - Yi, Bing-fang; Xia, Ting-ting; Niu, Ming-ming; Zhao, Zi-yu; Su, Qing-yang; Ming, Hong; Nie, Guo-xing
Abstract : A novel actinobacterium, designated strain CFH 90414 T, was isolated from sediment sampled at a saline lake in Yuncheng, Shanxi, PR China. The taxonomic position of the strain was investigated by using a polyphasic approach. Cells of strain CFH 90414 T were Gram-reaction-positive, aerobic and non-motile. Growth occured at 4−40 °C, pH 5.0−9.0 and in the presence of up to 0–3.0 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain CFH 90414 T was a member of the genus Agromyces . The 16S rRNA gene sequence similarity analysis indicated that strain CFH 90414 T was most closely related to Agromyces italicus JCM 14320 T (98.07 %) and Agromyces lapidis JCM 14321 T (97.18 %). The whole genome of CFH 90414 T was 3.64 Mb, and showed a G+C content of 71.5 mol%. The average nucleotide identity (ANI) values and digital DNA–DNA hybridization (dDDH) values between CFH 90414 T and the other species of the genus Agromyces were found to be low (ANI <78.99 % and dDDH <22.9 %). The whole-cell sugars were rhamnose, mannose, ribose, glucose and galactose. The isolate contained l -2, 4-diaminobutyric acid, d -alanine, d -glutamic acid and glycine in the cell-wall peptidoglycan. The predominant menaquinone was MK-12. The major cellular fatty acids were anteiso-C15 : 0, anteiso-C17 : 0 and iso-C16 : 0 . The polar lipid profile contained diphosphatidylglycerol, phosphatidylglycerol and an unidentiﬁed glycolipid. On the basis of phenotypic, genotypic and phylogenetic data, strain CFH 90414 T is considered to represent a novel species of the genus Agromyces, for which the name Agromyces agglutinans sp. nov. is proposed. The type strain is CFH 90414 T (=DSM 105966 T =KCTC 49062 T ).